OPERATION OF LIGHTS AND FAN USING INFRA RED WIND - Amzah Amzah; Ir. Irwan Nirmara MMSi (Jurnal Sistem Komputer, 2001)
Operation of lights and fans in a room need to be considered for use as needed, thencreated a device operation of lights and fans by using infrared sensors that workbased on the number of people who are in a room. Infrared sensor will detect peopleentering and those who came out, then the detection results will be displayed onseven segment LED.This final result was exhibited by a model of four lights and the fan berukut displayand sensor.